2016
DOI: 10.1021/acssuschemeng.6b01527
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Useless Iron Rust into Uniform α-Fe2O3 Nanospheres: A Smart Way to Make Sustainable Anodes for Hybrid Ni–Fe Cell Devices

Abstract: The large amount of iron rust yielded in steel industries is undoubtedly a useless and undesired product since its substantial formation and recycle/smelting would give rise to enormous financial costs and environmental pollution issues. To best reuse such rusty wastes, we herein propose a smart and applicable method to convert them into uniform α-Fe 2 O 3 nanospheres. Only after a simple and conventional hydrothermal treatment in HNO 3 solution, nearly all of the iron rust can evolve into sphere-like α-Fe 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 39 publications
0
44
0
Order By: Relevance
“…Zhu et al synthesized the α-Fe 2 O 3 nanospheres with the average diameter of 30 nm as shown in Figure 5a from the iron rust wastes using a costeffective and reliable way. [55] This revolutionary strategy was relatively low-cost and controllable, and could not only avoid high energy consumption but also relieve environmental pollution problems. With the small size, the as-built α-Fe 2 O 3 nanosphere could bring more active sites for electrochemical reactions and greatly increase the specific energy density.…”
Section: Iron Oxidesmentioning
confidence: 99%
“…Zhu et al synthesized the α-Fe 2 O 3 nanospheres with the average diameter of 30 nm as shown in Figure 5a from the iron rust wastes using a costeffective and reliable way. [55] This revolutionary strategy was relatively low-cost and controllable, and could not only avoid high energy consumption but also relieve environmental pollution problems. With the small size, the as-built α-Fe 2 O 3 nanosphere could bring more active sites for electrochemical reactions and greatly increase the specific energy density.…”
Section: Iron Oxidesmentioning
confidence: 99%
“…It can be seen that the attained results pointed out that the value of magnetization decreases regularly with the increasing concentration of AV extract. The reduction in magnetization (Ms) value of the green synthesized iron oxide nanostructures related to the bulk materials is mainly ascribed to the nano-sized particles [41]. This significant decrease in magnetization values are mainly attributed to the presence of higher amount of AV extract on the surface of γ-Fe 2 O 3 nanostructures.…”
Section: Electrocatalytic Activity Of Ua On γ-Fe2o3 Nanostructures Momentioning
confidence: 99%
“…Among various aqueous batteries, the alkaline Ni/ Fe battery has attracted much attention because Ni and Fe are earth-abundant, ecofriendly, and rather cheap compared with other alternatives [8]. Despite these merits, the relatively low power/energy density and short cycle life of Ni/Fe battery limit their wide applications [9,10]. To improve their performance, delicate design and synthesis of nanostructured electrodes have been widely reported [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%